Occupational Health Challenges among Hotel Housekeepers - Iing, Iing; Mariawati, Ade Sri; Duana, I Made Kerta (The Indonesian Journal of Occupational Safety and Health, 2025)
Introduction: Hotel housekeepers face several occupational health hazards, including physical, emotional, and environmental stressors. These workers usually face various obstacles, such as physical strain, emotional stress, low income, etc. However, there has been minimal examination of these difficulties. This review aimed to investigate the occupational health challenges faced by hotel housekeepers. Method: A systematic review was carried out during August and September 2024, using databases such as Google Scholar, PubMed, and ScienceDirect. The search focused on research published between 2014 and 2024, including keywords such as "occupational health, health challenges, housekeepers." After selecting publications based on inclusion and exclusion criteria, seven relevant studies were chosen for analysis. The review adhered to PRISMA criteria to achieve a thorough examination of the selected literature. Results: In accordance to the review, housekeepers commonly face physical pain, worry, and stress as a result of their employment. Many people relied on medication to keep working, despite the difficulty of taking sick days owing to job uncertainty. Low wages, along with inadequate equipment, fueled perceptions of abuse. Housekeepers were also exposed to dangerous substances, which could pose health hazards. Discrimination and working stress were strongly associated with chronic health issues. Conclusion: Our present review indicates that housekeepers experienced four key hurdles, including workplace concerns, employment security, physical and mental health issues. To ensure employees' health and well-being, employers should address wage discrepancies, provide proper work equipment, limit exposure to harmful chemicals, and give mental health support.